Acute inhibition of superoxide formation and Rac(1) activation by nitric oxide and iloprost in human vascular smooth muscle cells in response to the thromboxane A(2) analogue, U46619 - Muzaffar, S. (2008)
BACKGROUND: The over-production of superoxide ([Formula: see text]) derived from NADPH oxidase (NOX) plays a central role in cardiovascular diseases. By contrast, nitric oxide (NO) and prostacyclin (PGI(2)) are vasculoprotective. The effect of the NO donor, NONOate and iloprost on [Formula: see text] formation, p47(phox) and Rac(1) activation in human vascular smooth muscle cells (hVSMCs) was investigated. METHODS: hVSMCs were incubated with 10 nM thromboxane A(2) analogue, U46619 for 16 h, and then with apocynin (a NOX inhibitor), NONOate or iloprost for 1 h and [Formula: see text] measured spectrophometrically. The role of cyclic AMP and cyclic GMP was examined by co-incubation of drugs with protein kinase (PK) A and G inhibitors listed above. Rac(1) was studied using pull-down assays. RESULTS: NONOate and iloprost inhibited [Formula: see text] formation, acutely, effects blocked by inhibition of PKG and PKA, respectively. Rac(1) and p47(phox) activation and translocation to the plasma membrane was completely inhibited by NONOate and iloprost, effects again reversed by co-incubation with PKG or PKA inhibitors. CONCLUSIONS: NO and PGI(2) block the acute activity of NOX in hVSMCs via the cGMP–PKG axis (for NO) and by the cAMP–PKA axis (for iloprost) through inhibition of Rac(1) and p47(phox) translocation. These findings have implications in the pathophysiology and treatment of CVD.